DINAMIKA KEHIDUPAN ANAK DALAM KELUARGA PEKERJA KULI BANGUNAN DI DESA BUNIARA - Sendi Muhamad Fikri (Jurnal Sosiologi UPR, 2025)
This study aims to explore the dynamics of children's lives in families of construction laborers in Buniara Village. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and documentation study. The findings reveal that economic limitations force children to leave school and help with the family economy, leading to vulnerability to negative social behaviors. The role of the family in the socialization and education of children is not optimal, and the children’s future aspirations often conflict with economic realities. This study highlights the need for educational assistance and social protection programs at the village level.